Strategic evaluation of the black soldier fly maggot supply chain for sustainable agribusiness development - Inez Damayanti; Sindy Nur Cahyaningsih; Ummala Azahra Oktawidia; Rizka Amarylis Shifany (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: Optimal and efficient management is needed in handling food waste so that it does not become an environmental problem that impacts global warming, one of which is in Surakarta. One solution is to use maggots derived from black soldier fly larvae for food waste management. The importance of the role of maggots is not in line with its supply chain in Surakarta City, so the operation system is not optimal. This study aims to evaluate how the maggot supply chain in Surakarta is illustrated and provide strategies for the sustainability of the maggot supply chain in Surakarta amid various existing obstacles. Methods: This study uses qualitative descriptive techniques with purposive sampling for the selection of informants and experts and continues with analytical techniques using ISM-MICMAC and AHP. Findings: The ISM–MICMAC results identify a four-level hierarchical structure of the BSF maggot supply chain in Surakarta. Labor and technology are the main driver variables with strong driving power and low dependency, playing a crucial role in system performance. Weather factors act as external drivers requiring effective risk mitigation. Operational factors, including feed availability, market demand, and supply chain cooperation, are highly dependent on higher-level drivers, while pest disturbance appears as a purely consequential variable. The absence of linkage variables indicates a relatively stable system structure. Overall, strengthening labor, technology adoption, and climate adaptability is key to achieving a resilient and sustainable maggot supply chain. Conclusion: The evaluation of the maggot supply chain in Surakarta City can be divided based on the priority numbers to be paid more attention. There needs to be synergy of cooperation between supply chain actors to ensure the sustainability of production in the future. Novelty/Originality of this article: The novelty of this study is that there is no research on the evaluation and strategy of the maggot supply chain in the city of Surakarta as well as the combination of analysis methods using the ISM-MICMAC and AHP approaches.